Implementasi Spiritual Emotional Freedom Technique (Seft) Pada Pasien Gagal Ginjal Kronis Yang Menjalani Terapi Hemodialisis - Rani Febriyanti; Ambar Relawati; Indri Setiyawati (STIKes Ibnu Sina Ajibarang, 2024)
Patients with CKD undergoing HD must deal with several psychosocial issues that make their treatment process extremely difficult. It is anticipated that spiritual well-being will enhance patients' mental health and lessen the likelihood that they may experience anxiety and depression. In CKD patients undergoing HD, SEFT therapy helps lessen psychological and physical issues brought on by emotional and psychosomatic diseases. The purpose of this study is to ascertain whether using SEFT therapy can raise the spiritual well-being of CKD patients receiving HD at the PKU Muhammadiyah Gamping Hospital's hemodialysis unit. Method: This research design is a case study with a nursing care approach. There were two respondents in this study and sampling was carried out using a purposive sampling technique with inclusion criteria. Data analysis in this research was carried out using descriptive analysis methods. The instrument used in this research was the Spiritual Well-Being Scale (SWBS). Results: After being given SEFT therapy for 15–25 minutes over three meetings, there was an increase in the spirituality level scores of the research respondents, where the SWBS score of the first respondent increased by seven scores, while for the second respondent, the SWBS score increased by six scores. Conclusion: SEFT therapy can improve SWBS scores in HD patients at PKU Muhammadiyah Gamping Hospital. Suggestion: To maximize research results, SEFT therapy can be used in the field of clinical nursing practice to support the care of CKD patients undergoing HD by taking into account factors like the respondent's age, physical and psychological condition, the amount of time they have undergone HD, their spirituality, the length and frequency of application of the therapy, as well as the surrounding environment.